2018
DOI: 10.3390/nu10091204
|View full text |Cite
|
Sign up to set email alerts
|

Metabolaid® Combination of Lemon Verbena and Hibiscus Flower Extract Prevents High-Fat Diet-Induced Obesity through AMP-Activated Protein Kinase Activation

Abstract: Lemon verbena (Lippia citriodora) has been used as a food spice, cosmetic, and in traditional medicine formulations to treat asthma and diabetes in South America and Southern Europe. Hibiscus flower (Hibiscus sabdariffa L.) is used in traditional Chinese medicine in the form of a tea to treat hypertension and inflammation. In the present study, we examined the synergistic effects of a formula of Metabolaid® (MetA), a combination of lemon verbena and hibiscus-flower extracts, on obesity and its complications in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 45 publications
6
45
0
Order By: Relevance
“…Despite not obtaining statistically signi cant results, it seems evident that treatment with Lc-Hs is able to reduce food intake, as shown in adlibitum intake, appetite sensation and Ghrelin concentration in overweight and obese patients. The present data reinforces the idea that an adjuvant treatment with polyphenols can favorably affect glucose intake and regulation, adipogénesis, lipolysis, lipid metabolism, appetite control and improve pathologies related to obesity due to AMPK pathway modulation (9,18). As well as the practice of physical exercise that help to reach caloric de cit, may be the best strategy for the treatment of obesity given the nature of the disease (43).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Despite not obtaining statistically signi cant results, it seems evident that treatment with Lc-Hs is able to reduce food intake, as shown in adlibitum intake, appetite sensation and Ghrelin concentration in overweight and obese patients. The present data reinforces the idea that an adjuvant treatment with polyphenols can favorably affect glucose intake and regulation, adipogénesis, lipolysis, lipid metabolism, appetite control and improve pathologies related to obesity due to AMPK pathway modulation (9,18). As well as the practice of physical exercise that help to reach caloric de cit, may be the best strategy for the treatment of obesity given the nature of the disease (43).…”
Section: Discussionsupporting
confidence: 84%
“…Mechanisms include; Increased peroxisome proliferator-activated receptor (PPAR-γ) which promotes acid β-oxidation (38), inhibition of synthesis of malonyl-Coa (39) fatty acids precursor, increased CPT-1 protein which facilitate transport of fatty acids into mitochondria (38), activation of AMP-activated protein kinase (AMPK) pathway improving the glucose uptake in the cell (40) and thus insulin resistance. For example, scienti c evidence has sown that certain plan-derivate such a Hibiscus sabadarrifa or Lippia citriodora can modulate different metabolic pathways and have certain effects activating the AMPK pathway, favoring lipolysis and fat loss (9,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basis of the present work is due to the lack of scientific reports on humans besides the promising use of Lippia citriodora and Hibiscus sabdariffa, recognized for their high content of polyphenols, powerful antioxidant molecules that may prevent several disease factors such as hypertension, oxidative stress, dyslipidemia, lipid mobilization, or endothelial stiffness [6]. The present Hibiscus sabdariffa and Lippia citriodora (HS-LC) formula has been previously studied in various clinical studies, in order to help induce weight loss during a controlled diet program [15,16]. The aim of the present study is to determine if the supplementation with Lippia citriodora and Hibiscus sabdariffa is useful for the treatment of obesity and/or weight control in the absence of a controlled diet.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that polyphenols from LC can ameliorate the metabolic alterations that occur in obesity by decreasing oxidative stress and mitochondrial dysfunction and modulating the expression or activity of some proteins involved in metabolic homeostasis and energy control, such as peroxisome proliferator-activated receptor alpha (PPARα) and fatty acid synthase (FASN) [14]. Evidence from cellular and animal models of obesity and from human trials suggests that the activation of AMP-activated protein kinase (AMPK) by LC polyphenols might be one of the mechanisms involved in the modulation of fat metabolism [6,13,17].…”
Section: Introductionmentioning
confidence: 99%